2017
DOI: 10.18438/b8r645
|View full text |Cite
|
Sign up to set email alerts
|

What Do Australian Library and Information Professionals Experience as Evidence?

Abstract: Objective -This article presents the findings of a project which established an empirical basis for evidence based library and information practice (EBLIP). More specifically, the paper explores what library and information professionals experienced as evidence in the context of their professional practice.Methods -The project consisted of two sub-studies. The public library sub-study was conducted using ethnography. Over a 5-month period, a member of the research team travelled to a regional public library on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Koufogiannakis grouped sources of evidence into either "hard" or "soft," where "hard" included sources that could be easily shared, were "written, concrete information" that was generally accepted as evidence, and "soft" included sources that focused on experience or knowledge or others that allowed a "real-life connection" to context (2012, p. 11). This broad interpretation of "evidence" was consistent with findings reported by Gillespie et al (2017), which included observations, feedback and statistics recognised as evidence by practitioners. Experiences of evidence based practice have been found to not always be a straight-forward or linear process, but "holistic" in being evidence based LIS professionals (Gillespie, 2014;Koufogiannakis, 2013;Koufogiannakis, 2015;Luo, 2018;Miller, Partridge, Bruce, Yates, & Howlett, 2017).…”
Section: Understanding Evidence Based Practice In the Lis Professionasupporting
confidence: 87%
See 1 more Smart Citation
“…Koufogiannakis grouped sources of evidence into either "hard" or "soft," where "hard" included sources that could be easily shared, were "written, concrete information" that was generally accepted as evidence, and "soft" included sources that focused on experience or knowledge or others that allowed a "real-life connection" to context (2012, p. 11). This broad interpretation of "evidence" was consistent with findings reported by Gillespie et al (2017), which included observations, feedback and statistics recognised as evidence by practitioners. Experiences of evidence based practice have been found to not always be a straight-forward or linear process, but "holistic" in being evidence based LIS professionals (Gillespie, 2014;Koufogiannakis, 2013;Koufogiannakis, 2015;Luo, 2018;Miller, Partridge, Bruce, Yates, & Howlett, 2017).…”
Section: Understanding Evidence Based Practice In the Lis Professionasupporting
confidence: 87%
“…Studies in a variety of contexts such as academic libraries, teacher librarianship, public and special libraries have explored conceptualizations and lived experiences of evidence based practice by LIS professionals. LIS professionals identify and use a variety of evidence types, beyond the research literature (Gillespie, Miller, Partridge, Bruce, & Howlett, 2017;Koufogiannakis, 2012). Koufogiannakis grouped sources of evidence into either "hard" or "soft," where "hard" included sources that could be easily shared, were "written, concrete information" that was generally accepted as evidence, and "soft" included sources that focused on experience or knowledge or others that allowed a "real-life connection" to context (2012, p. 11).…”
Section: Understanding Evidence Based Practice In the Lis Professionamentioning
confidence: 99%
“…Over the past decade, understanding evidence-based practice in the library practitioners' context has evolved to a broader view of what constitutes as 'evidence'. In particular, research identified an appreciation of the complexities that impact on the implementation in day-to-day practice (Gillespie et al, 2017;Alisa Howlett & Howard, 2015;Koufogiannakis, 2011bKoufogiannakis, , 2012Luo, 2018). Findings from empirical studies (Gillespie et al, 2017;Koufogiannakis, 2011a) confirmed that library professionals identify and use a variety of evidence types, beyond the research literature and often combine different types, to inform their daily practice.…”
Section: Sources Of Evidencementioning
confidence: 96%
“…In particular, research identified an appreciation of the complexities that impact on the implementation in day-to-day practice (Gillespie et al, 2017;Alisa Howlett & Howard, 2015;Koufogiannakis, 2011bKoufogiannakis, , 2012Luo, 2018). Findings from empirical studies (Gillespie et al, 2017;Koufogiannakis, 2011a) confirmed that library professionals identify and use a variety of evidence types, beyond the research literature and often combine different types, to inform their daily practice. Koufogiannakis (2011c) identified two other types of evidence that are valid as important and contextual sources of evidence for library and information service practitionerslocal evidence and professional knowledge.…”
Section: Sources Of Evidencementioning
confidence: 96%
See 1 more Smart Citation